Existential behavioral therapy for informal caregivers of palliative patients: Barriers and promoters of support utilization. Issue 3 (6th June 2014) - Thurn, Tamara; Brandstätter, Monika; Fensterer, Veronika; Küchenhoff, Helmut; Fegg, Martin Johannes
Abstract: Objective: Several interventions have been developed during recent years to support informal caregivers of palliative patients. However, these trials reported low enrollment rates. Employing a newly developed group intervention, existential behavioral therapy (EBT), one study reported that only 13.6% of approached informal caregivers participated. The purpose of our present study was to identify the reasons for this low enrollment rate in order to improve future support designs. Method: All participants in the EBT trial (intervention vs. standard-care control group) as well as those who declined participation during a 4-month recruitment period were studied prospectively over 12 months. Andersen's behavioral model of healthcare service use was employed to identify group differences between acceptors and decliners: predisposing (age, gender, education, family status, relationship), enabling (social support, distance to hospital, caring vs. bereaved), and need factors (psychological distress, quality of life) were evaluated in a binary-logistic model. Results: Some 94 decliners were compared to 160 EBT participants ( n = 81 intervention, n = 79 control). Caregivers who took part were significantly more distressed and suffered from a lower quality of life compared to decliners. Not only these need factors but also predisposing (age <55 years) and enabling (use of social/professional support, familiarity with caregiving institution) factors were associated with EBT utilization. At the 12-month follow-up, EBT intervention participants reported greater quality of life improvements than decliners or controls ( p = 0.05). While all groups had mean anxiety scores below the cutoff at 12-month follow-up, decliners showed better improvement in anxiety compared to EBT participants (intervention p = 0.04, controls p = 0.03). Significance of results: On average, decliners are less burdened: they may be more resilient, may have better coping strategies, or already have a sufficient support network in place. Screening caregivers with regard to their experienced quality of life and targeting those in need, especially younger caregivers with low levels of quality of life, may help to allocate resources more appropriately.